2015
DOI: 10.18632/oncotarget.4725
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 is involved in the acquisition and maintenance of a stem cell-like/aggressive phenotype in prostate cancer cells with acquired resistance to zoledronic acid

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 99 publications
5
49
0
1
Order By: Relevance
“…7 The role of this protein in PCa development and progression is still debated, however we have recently showed that the protein plays a significant part in regulating aggressive behaviors of a chemoresistant sub-line of DU145 PCa cells. 9 In the present study, we demonstrated that ANXA1 is able to mediate some of the pro-oncogenic hypoxia-related events in vitro.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…7 The role of this protein in PCa development and progression is still debated, however we have recently showed that the protein plays a significant part in regulating aggressive behaviors of a chemoresistant sub-line of DU145 PCa cells. 9 In the present study, we demonstrated that ANXA1 is able to mediate some of the pro-oncogenic hypoxia-related events in vitro.…”
Section: Discussionsupporting
confidence: 58%
“…31,32 and that the occurrence of this event in cancer cells possibly will result in the acquisition of a very aggressive phenotype characterized by the acquisition of augmented invasion capability and of stem-cell like features. 9 Therefore, we evaluated if ANXA1 could have a proinvasive role in LNCaP, DU145 and PC3 cell lines thanks to its ability to activate FPRs, as previously reported in pancreas and colon carcinomas. 18,33 We performed a matrigel invasion assay by stimulating or not LNCaP, DU145 and PC3 cells by administration of Ac2-26 peptide, the N-terminus mimetic peptide of ANXA1, of the natural FPR agonist N-FormylmethionyL-leucyL-phenylalanine (fMLP) peptide 30 and of 2 FPR antagonists, in normoxia and hypoxia conditions.…”
Section: Secretion Of Anxa1 Protein Has a Crucial Role During Hypoxiamentioning
confidence: 95%
See 3 more Smart Citations